The Effect of Capital Structure on the Financial Performance of Healthcare Companies on the Indonesia Stock Exchange: The Moderating Role of Macroeconomics (2021–2024) - Marli; Dwi Danesty Deccasari Danesty (LP2M IAIN Palopo, 2026)
This research is a causal associative quantitative study that aims to analyze the causal relationship between Capital Structure and Financial Performance variables with Macroeconomic Moderation. The population is 16 Main Board Healthcare and Developer companies listed on the IDX in 2021-2024. Using the SEM-PLS 4.0 analysis tool, the research results show that Macroeconomic Variables contribute positively and significantly to the company's Financial Performance, indicated by a path coefficient of 0.349. Conversely, Capital Structure has a negative and significant effect on Financial Performance with a coefficient of -0.419, indicating that an inefficient capital structure can reduce financial performance.